Recycling of Automotive Sheet Metal-Fibre Reinforced Plastic-Hybrid Structures - Siewers, Bernd; Lauter, Christian; Tröster, Thomas

Manufacturing of Hybrid Structures by Prepreg Press Technology - Lauter, Christian; Krooß, T.; Tröster, Thomas

Leichtbau mit Hybridstrukturen im Automobil - Tröster, Thomas; Lauter, Christian; Reuter, C.

On the Fatigue Behavior of TiAl6V4 Manufactured by Selective Laser Melting– Influence of Process Induced Defects - Leuders, S.; Riemer, A.; Niendorf, T.; Richard, H. A.; Tröster, Thomas

Effizienter Leichtbau durch gradierte Eigenschaften im Presshärteprozess - Marten, Thorsten; Block, Holger; Tröster, Thomas

Bewertung des Einflusses korrosiver Schädigung auf das Ermüdungsverhalten von CFK/Stahl-Hybridverbindungen - Riemer, A.; Leuders, S.; Richard, H. A.; Tröster, Thomas

Multilabel classification for exploiting cross-resistance information in HIV-1 drug resistence prediction - Heider, D.; Senge, Robin; Cheng, W.; Hüllermeier, Eyke (Bioinformatics)

Chest pain in primary care: is the localization of pain diagnostically helpful in the critical evaluation of patients? A cross sectional study. - Bösner, S.; Bönisch, K.; Haasenritter , J.; Schlegel, P.; Hüllermeier, Eyke; Donner-Banzhoff, N. (BMC Family Practice)

Diagnose im Kontext - eine erweiterte Perspektive - Haasenritter, J.; Viniol, A.; Becker, A.; Bösner, S.; Hüllermeier, Eyke; Senge, Robin; Donner-Banzhoff, N. (Zeitschrift für Evidenz, Fortbildung und Qualität im Gesundheitswesen (ZEFQ))

Hybrid Structures Consisting of Sheet Metal and Fibre Reinforced Plastics for Structural Automotive Applications - Lauter, Christian; Tröster, Thomas; Reuter, Corin (Advanced Composite Materials for Automotive Applications)

Direct Observation of Sub-Binomial Light - Bartley, Tim; Donati, Gaia; Jin, Xian-Min; Datta, Animesh; Barbieri, Marco; Walmsley, Ian A. (Physical Review Letters)

Strategies for enhancing quantum entanglement by local photon subtraction - Bartley, Tim; Crowley, Philip J. D.; Datta, Animesh; Nunn, Joshua; Zhang, Lijian; Walmsley, Ian (Physical Review A)

Requirements for two-source entanglement concentration - Vidrighin, Mihai; Bartley, Tim; Donati, Gaia; Jin, Xian-Min; Barbieri, Marco; Kolthammer, W. Steven; Datta, Animesh; Walmsley, Ian A. (Quantum Measurements and Quantum Metrology)

Evolving fuzzy pattern trees for binary classification on data streams - Shaker, A.; Senge, R.; Hüllermeier, Eyke (Information Sciences)

"Ihr betet an, was ihr nicht kennt" (Jo 4, 22) - Eine neue Sicht auf die Trinität - Krimphove, Dieter

Kommentar: MaComp Mindestanforderungen an die Compliance-Funktion und die weiteren Verhaltens-, Organisations- und Transparenzpflichten nach §§ 31 ff. WpHG für Wertpapierdienstleistungsunternehmen - Krimphove, Dieter; Kruse, Oliver

Europarecht inklusive CD-ROM mit Gesetzen, Urteilen, Hörfassung und interaktiven Falllösungen - Krimphove, Dieter

Visualization and Collaborative Editing of Simulation Models With Heterogeneous Clients: Implemented Into the Simulator D3FACT - Renken, Hendrik; Brandt, Sascha; Eichert, Felix A.; Klaas, Alexander (Volume 2: 32nd Computers and Information in Engineering Conference, Parts A and B)
Today’s simulation software normally has fixed, built-in editing and visualization views adapted to a specific problem domain. Often this monolithic concept prevents collaborative editing altogether. Even with more flexible concepts, editing simulation models with a heterogeneous set of clients is not possible. In this article we describe a flexible concept for collaborative editing of simulation models with heterogeneous clients, such as web-based, desktop and mobile clients. The clients may even show different editing views adapted to the user’s role. The concept we describe in this paper overcomes several problems: First we need to be able to connect and manage a set of heterogeneous clients in the simulation software. The very different user inputs from the connected clients then need to be processed, interpreted and combined to allow editing in a collaborative way for all users. At last we show a prototypical integration of the presented concept into our research platform d3fact.

Use both lanes: Multi-channel beaconing for message dissemination in vehicular networks - Klingler, Florian; Dressler, Falko; Cao, Jiannong; Sommer, Christoph (2013 10th Annual Conference on Wireless On-demand Network Systems and Services (WONS))

Spherical Visibility Sampling - Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Computer Graphics Forum)
Many 3D scenes (e.g. generated from CAD data) are composed of a multitude of objects that are nested in each other. A showroom, for instance, may contain multiple cars and every car has a gearbox with many gearwheels located inside. Because the objects occlude each other, only few are visible from outside. We present a new technique, Spherical Visibility Sampling (SVS), for real-time 3D rendering of such -- possibly highly complex -- scenes. SVS exploits the occlusion and annotates hierarchically structured objects with directional visibility information in a preprocessing step. For different directions, the directional visibility encodes which objects of a scene's region are visible from the outside of the regions' enclosing bounding sphere. Since there is no need to store a separate view space subdivision as in most techniques based on preprocessed visibility, a small memory footprint is achieved. Using the directional visibility information for an interactive walkthrough, the potentially visible objects can be retrieved very efficiently without the need for further visibility tests. Our evaluation shows that using SVS allows to preprocess complex 3D scenes fast and to visualize them in real time (e.g. a Power Plant model and five animated Boeing 777 models with billions of triangles). Because SVS does not require hardware support for occlusion culling during rendering, it is even applicable for rendering large scenes on mobile devices.

Evaluation of Rendering Algorithms Using Position-Dependent Scene Properties - Jähn, Claudius; Eikel, Benjamin; Fischer, Matthias; Petring, Ralf; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
In order to evaluate the efficiency of algorithms for real-time 3D rendering, different properties like rendering time, occluded triangles, or image quality, need to be investigated. Since these properties depend on the position of the camera, usually some camera path is chosen, along which the measurements are performed. As those measurements cover only a small part of the scene, this approach hardly allows drawing conclusions regarding the algorithm's properties at arbitrary positions in the scene. The presented method allows the systematic and position-independent evaluation of rendering algorithms. It uses an adaptive sampling approach to approximate the distribution of a property (like rendering time) for all positions in the scene. This approximation can be visualized to produce an intuitive impression of the algorithm's behavior or be statistically analyzed for objectively rating and comparing algorithms. We demonstrate our method by evaluating performance aspects of a known occlusion culling algorithm.

Real-Time 3D Rendering of Heterogeneous Scenes - Petring, Ralf; Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
Many virtual 3D scenes, especially those that are large, are not structured evenly. For such heterogeneous data, there is no single algorithm that is able to render every scene type at each position fast and with the same high image quality. For a small set of scenes, this situation can be improved if different rendering algorithms are manually assigned to particular parts of the scene by an experienced user. We introduce the Multi-Algorithm-Rendering method. It automatically deploys different rendering algorithms simultaneously for a broad range of scene types. The method divides the scene into subregions and measures the behavior of different algorithms for each region in a preprocessing step. During runtime, this data is utilized to compute an estimate for the quality and running time of the available rendering algorithms from the observer's point of view. By solving an optimizing problem, the image quality can be optimized by an assignment of algorithms to regions while keeping the frame rate almost constant.

A3.2 - Design, modeling and identification of an ultrasonic composite transducer for target impedance independent short pulse generation - Bause, F.; Rautenberg, J.; Henning, Bernd

3.2 - Infrared reflectance measurements of thin films with time variable surface roughness or texture - Hoof, C.; Wetzlar, D.; Henning, Bernd

Messsystem zur Bestimmung akustischer Kenngrößen stark absorbierender, transversal isotroper Kunststoffe - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

Multi Reflection of Lamb Wave Emission in an Acoustic Waveguide Sensor - Schmitt, Martin; Olfert, Sergei; Rautenberg, Jens; Lindner, Gerhard; Henning, Bernd; Reindl, Leonhard (Sensors)

Detection of coatings within liquid-filled tubes and containers by mode conversion of leaky Lamb waves - Schmitt, M.; Schmidt, K.; Olfert, S.; Rautenberg, J.; Lindner, G.; Henning, Bernd; Reindl, L. M. (Journal of Sensors and Sensor Systems)
Abstract. In this paper, a new acoustic sensor principle for coating detection within liquid-filled tubes and containers based on mode conversion of leaky Lamb waves is introduced. Leaky Lamb waves are excited and detected by single-phase transducers, which are attached on the outer side of a tube or container. By transmission time and amplitude measurements, coating formation within the liquid-filled tube and container is detected non-invasively. This new sensor principle is subdivided into the separate considerations of Lamb wave excitation, mode conversion and inverse mode conversion. The Lamb wave excitation by a single-phase transducer is visualized by scanning laser Doppler vibrometer imaging. The mode conversion process of leaky Lamb waves is measured by membrane hydrophone measurements and Schlieren visualization; afterwards, the measured emission angles are compared with the theoretical one. The inverse mode conversion process of pressure waves back to leaky Lamb waves is visualized by Schlieren images. By merging the results of Lamb wave excitation, mode conversion and inverse mode conversion, the new sensor concept is explained. Theoretical considerations and measurement results of adhesive tape coating inside a liquid-filled plastic tube and a liquid-filled stainless steel container verify the new acoustic sensor principle. Finally the measuring sensitivity and the technical realization are discussed.

Luftultraschall-Abstandsmessung mit digitaler Signalverarbeitung zur Verkürzung des Mindestabstandes - Schröder, Andreas; Henning, Bernd (tm - Technisches Messen)

B5.4 - Signal Processing for Single Transducer Distance Measurement Applications to Reduce the Blind Zone - Schröder, A.; Henning, Bernd

Utilizing ultrasound material parameter determination for the characterization of different stages of ageing in Polyamide 6 - Bause, Fabian; Budde, Christopher; Rautenberg, Jens; Henning, Bernd; Moritzer, Elmar
The condensation polymer Polyamide 6 (PA 6) is a thermoplastic resin with high tensile strength and rigidity at comparatively low costs for raw material and processing. This is why PA 6 is a common material for the production of ropes, gears or bearings. Apart from that, a relative new application is the thermoforming of glass fibre laminate sheets with PA 6 as matrix material. The prediction the rest of life period of such high-tech materials is still a research objective. A first step, and also part of this contribution, is the nondestructive investigation of the matrix material. The ageing of PA 6 is mainly affected by thermo- and photo-oxidation as well as post-condensation, which e.g. results in a change of physical properties. For this contribution the acoustical and mechanical material parameters of artificially aged PA 6 have been determined with high frequency ultrasound (1 MHz) and quasi-static experiments. We will give a short description of both experimental setups as well as the ageing procedure. Finally we will discuss the correlation between the experimental results, finding that there is a good correlation between sound velocity and tensile strength.

Ultrasonic Waveguide Signal Decomposition Using the Synchrosqueezed Wavelet Transform for Modal Group Delay Computation - Bause, Fabian; Huang, Boqiang; Kunoth, Angela; Henning, Bernd
Due to the modal behavior of geometrically bounded media, ultrasonic guided waves propagate in waveguides as a combination of multiple dispersive wave packets, which can be simulated as a PDE-problem. Given an excitation in time and space, multiple eigen-modes derived from solving the PDE may propagate each with different dispersion characteristics and weight. Considering a broad-band pulse exciting from one side of a hollow cylindrical waveguide, the received signal at the other side consists of all propagating eigen-modes that can be considered approximately as the narrow band signals. The synchrosqueezed wavelet transform (SWT) is employed to sharpen the time-frequency representation (TFR) of the received waveguide signal. Using a ridge detection algorithm, we successively separate the synchrosqueezed TFR into several narrow band TFRs which can be identified as oscillatory components with time-varying frequency. Then those separated TFRs are reconstructed as narrow band signals using the inverse SWT. Based on an analytical model of the waveguide, we observe that the decomposed signals are similar to those dominant eigen-modes simulated above. Moreover, also the group delay and, therefore, the group velocity of each decomposed signal can be estimated well. This is of high interest when analyzing the characteristic of a given waveguide, such as acoustical property measurements or non-destructive testing.

Utilizing interval-Newton approach for the reliable computation of roots in analytical waveguide modeling - Bause, Fabian; Unverzagt, Carsten; Walther, Andrea; Henning, Bernd

Reliable Computation of Roots in Analytical Waveguide Modeling Using an Interval-Newton Approach and Algorithmic Differentiation - Bause, Fabian; Walther, Andrea; Rautenberg, Jens; Henning, Bernd (Transactions on Ultrasonics, Ferroelectrics, and Frequency Control)

Modellgestützte NIR-Materialfeuchtemessung mittels Multidetektoranordnung - Hoof, Christian; Wetzlar, Dietmar; Henning, Bernd (Technisches Messen)
Zur berührungslosen Materialfeuchtebestimmung wird unter anderem die Infrarotreflexionsmessung genutzt. Diese nichtinvasive und schnelle Methode ist geeignet sowohl zur Bestimmung der Feuchte von Schüttgütern als auch zur Charakterisierung von Trocknungsprozessen von Lacken. Die reflektierte Strahlung ist dabei abhängig von Absorption und Streuung in der Beschichtung sowie von den temporären und lokalen Reflexionseigenschaften des Messobjektes. ln dieser Untersuchung ist ein experimenteller Aufbau zur simultanen Messung der gerichteten und der diffus reflektierten Strahlungsanteile realisiert.

Untersuchung zum Trocknungsverhalten poröser Materialien durch NIR-Reflexionsmessungen - Hoof, Christian; Wetzlar, Dietmar; Henning, Bernd

A modified electrode topology with increased sensitivity of electrical impedance to piezoelectic material parameters - Kulshreshtha, Kshitij; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

Improved Signal Processing for an Ultrasonic Distance Sensor with Reduced Blind Zone - Schröder, Andreas; Henning, Bernd (Proceedings of the International Conference on Acoustics)
Single transducer distance sensors have a blind zone because normally the electrical received signal cannot be detected during transmitting. There are several approaches to realize a simultaneous transmit and receive operation. Digital signal processing is the best solution for narrow band systems (air ultrasound transducer) especially when the transmitted signal is coded. Thereby a mathematical model is used to estimate the electrical received signal. A drawback of the digital signal processing is the required computing time to estimate the model and the time of flight of an echo. In this contribution the computing time is reduced significantly by using base band signals for the signal processing. The signal-processing is subdivided into the following steps: Preprocessing, model identification, estimation of the received signal and echo detection. Beside the model identification the signal-preprocessing is an important part of the system. It depends on the time of flight of an echo (close echo, far echo) and the state of the system (single measurement, averaging). The whole system is evaluated with measurements using a 40 kHz air ultrasound transducer in front of a reflector with varying distances between 0 mm and 1000 mm.

Modified electrode shape for the improved determination of piezoelectric material parameters - Unverzagt, Carsten; Rautenberg, Jens; Henning, Bernd; Kulshreshtha, Kshitij (Proceedings of the 2013 International Congress on Ultrasonics)

A Comparison of Alternative Ways to Identify Singular Matrices - Walther, Andrea; Bause, Fabian; Henning, Bernd

Adaptive Test and Diagnosis of Intermittent Faults - Cook, Alejandro; Rodriguez Gomez, Laura; Hellebrand, Sybille; Indlekofer, Thomas; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Learning to rank lexical substitutions - Szarvas, G.; Busa-Fekete, Robert; Hüllermeier, Eyke (In Proceedings EMNLP-2013 Conference on Empirical Methods in Natural Language Processing, Seattle, USA)

Optimizing the F-measure in multi-label classification: Plug-in rule approach versus structured loss minimization - Dembczynski, K.; Jachnik, A.; Kotlowski, W.; Waegeman, W.; Hüllermeier, Eyke (in Proceedings ICML-2013, 30th International Conference on Machine Learning, Atlanta, USA)

Top-k selection based on adaptive sampling of noisy preferences - Busa-Fekete, Robert; Szoreny, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (in Proceedings ICML-2013, 30th International Conference on Machine Learning, Atlanta, USA)

Preference-based CBR: General ideas and basic principles - Hüllermeier, Eyke; Cheng, W. (in Proceedings IJCAI-13, 23rd international Joint Conference on Artificial Intelligence, Beijing, China)

Rule chains for visualizing evolving fuzzy rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (in Proceedings CORES 2013, 8th International Conference on Computer Recognition Systems, Wroclaw, Poland)

Recovery analysis for adaptive learning from non-stationary data streams - Shaker, Ammar; Hüllermeier, Eyke (in Proceedings CORES 2013, 8th International Conference on Computer Recognition Systems, Wroclaw, Poland)

BlogForever: From web archiving to blog archiving - Kalb, Hendrik; Lazaridou, Paraskevi; Banos, Vangelis; Kasioumis, Nikos; Trier, Matthias (INFORMATIK 2013 – Informatik angepasst an Mensch, Organisation und Umwelt)

Establishing interoperability of a blog archive through linked open data - Kalb, Hendrik; Lazaridou, Paraskevi; Trier, Matthias (INFORMATIK 2013 – Informatik angepasst an Mensch, Organisation und Umwelt)

Influence and Dissemination Of Sentiments in Social Network Communication Patterns - Hillmann, Robert; Trier, Matthias (ECIS 2013 Proceedings)
Previous research suggests the existence of sentiments in online social networks. In comparison to real life human interaction, in which sentiments have been shown to have an influence on human behaviour, it is not yet completely understood which mechanisms explain how sentiments influence users in online environments. We develop a theoretical framework that tries to bridge the gap between social influence theories that focus on offline interactions on one hand and online interaction in social networks on the other hand. We then test our hypothesis about the influence and dissemination of sentiments in a quantitative analysis that is based on retrieved textual messages of communication patterns in over 12000 online social networks. Our empirical results suggest a general influence of sentiments on node communication patterns that is evidenced by increased occurrences of subsequent messages that express the same sentiment polarization. We interpret these findings and suggest future research to advance our currently limited theories that assume perceived and generalized social influence to path-dependent social influence models that consider actual behaviour.
Keywords: Social Network Analysis; Sentiment Analysis; Communication Patterns

Interoperability of Web Archives and Digital Libraries: A Delphi Study - Kalb, Hendrik; Lazaridou, Paraskevi; Pinsent, Edward; Trier, Matthias (Proceedings of the 10th International Conference on Preservation of Digital Objects)
The interoperability of web archives and digital libraries is crucial to avoid silos of preserved data and content. While various researches focus on specfic facets of the challenge to interoperate, there is a lack of empirical work about the overall situation of actual challenges. We conduct a Delphi study to survey and reveal the insights of experts in the field. Results of our study are presented in this paper to enhance further research and development efforts for interoperability.
Keywords: Interoperability; Web Archives; Digital Libraries; Delphi Study